Predictors of Over-Anticoagulation in Warfarin Users in the UK General Population: A Nested Case–Control Study in a Primary Health Care Database - Martín-Pérez, Mar; Gaist, David; de Abajo, Francisco J.; García Rodríguez, Luis A. (Thrombosis and Haemostasis, 2019)
Background Many patients on warfarin therapy often present with supratherapeutic international normalized ratio (INR) levels, resulting from the influence of several patient-specific factors, which have been associated with adverse outcomes.Objective This article aims to identify risk factors for over-anticoagulation (INR levels ≥4) in a cohort of patients taking warfarin.Methods A cohort of warfarin users aged 18 to 85 years from January 2005 to April 2013 was identified in The Health Improvement Network U.K. primary care database (N = 12,506). A random date was assigned to all patients within their eligible person-time (index date), and a nested case–control analysis was performed with individuals presenting a first episode of INR level ≥4 after the index date used as cases (N = 699) and patients with non-supratherapeutic INR values (≤3) as controls (N = 9,798). Using unconditional logistic regression models, odds ratios with 95% confidence intervals were calculated adjusted for potential confounders. Two sensitivity analyses were performed with alternative definitions of over-anticoagulation (INR levels ≥5 or > 3).Results Among the factors examined, the strongest predictors of over-anticoagulation were warfarin indication (in particular, valvular atrial fibrillation and valve replacement), renal failure (with the risk increasing steeply with decreasing estimated glomerular filtration rate), cancer, anaemia, respiratory infections treated with antibiotics, chronic obstructive pulmonary disease treated with β2-agonists, polypharmacy (≥10 medications), low socio-economic status and residency in rural areas. Similar results were obtained when supratherapeutic levels were defined as INR ≥5 or, alternatively, as INR > 3.Conclusion Predictors of supratherapeutic INR levels found in this study might help physicians identify patients where closer INR monitoring is warranted.
Keywords: database; epidemiological studies; international normalized ratio; risk factors; warfarin